Fractal analysis of the fractal ultra-wideband signals - Chernogor, L.F.; Lazorenko, O.V.; Onishchenko, A.A. (Вопросы атомной науки и техники, 2015)
The results of fractal analysis of the fractal ultra-wideband (FUWB) signals were proposed. With usage of the continuous wavelet transform the time-frequency structure of that signals was investigated. Calculating the box and the regularization dimensions for each model signal with various its parameters values, three different estimators were applied. The optimal estimations of the fractal dimension value for each FUWB signal model were defined.